Taking climate change seriously: An analysis of op-ed articles in Spanish press. (October 2017) - Domínguez, Martí; Lafita, Íngrid; Mateu, Anna
In this article, we study the evolution of opinion genres regarding climate change in three Spanish newspapers ( El País, El Mundo, and ABC ). Analyzing the op-ed articles in these newspapers, we observe a significant change in the evolution of opinion. While denialism was very present in conservative press in 2007, 7 years later it is almost absent from El Mundo, and its presence in ABC is much lower and inactive: this shows that scientific consensus has prevailed over time and Spanish denialism has weakened, exclusively supported by political arguments by the most conservative parties.